Concomitant Factors Leading to an Atypical Osteonecrosis of the Jaw in a Patient with Multiple Myeloma - Jaume Miranda-Rius; Lluís Brunet-Llobet; Eduard Lahor-Soler; Josep Anton Giménez-Rubio (Case Reports in Medicine)
Osteonecrosis of the jaw (ONJ) is a site specific osseous pathology, characterized by chronic exposed bone in the mouth, which needs to be reinforced periodically within the medical literature. ONJ is a clinical entity with many possible aetiologies and its pathogenesis is not well understood. The risk factors for ONJ include bisphosphonates treatments, head and neck radiotherapy, dental procedures involving bone surgery, and trauma. Management of ONJ has centred on efforts to eliminate or reduce severity of symptoms, to slow or prevent the progression of disease, and to eradicate diseased bone. This case describes a rare case of ONJ in a 64-year-old Caucasian male diagnosed with multiple myeloma stage III. The lesion was related to a traumatic injury during mastication. Eighteen months ago in the same area the molar 37 was extracted, achieving a complete satisfactory healing, when only 2 doses of zoledronic acid had been administered. Actinomyces bacterial aggregates were also identified in the microscopic analysis. The management of this osteonecrotic lesion included antibiotic treatment and chlorhexidine topical gel administration. The evolution was monitored every two weeks until patient’s death. The authors provide a discussion of the etiology, pathogenesis, diagnosis, and management. This case report may shed light on the controversies about concomitant factors and mechanisms inducing ONJ.